Recent Advances of Salivary Gland Biopsy in Sjögren's Syndrome - Liao, Rui; Yang, Hai-Tao; Li, Heng; Liu, Li-Xiong; Li, Kai; Li, Jing-Jing; Liang, Jie; Hong, Xiao-Ping; Chen, Yu-Lan; Liu, Dong-Zhou (Frontiers in Medicine, 2022)
Sjögren’s syndrome (SS) is a chronic, systemic, inflammatory autoimmune disease characterized by lymphocyte proliferation and progressive damage to exocrine glands. The diagnosis of SS is challenging due to its complicated clinical manifestations and nonspecific signs. Salivary gland biopsy plays an important role in the diagnosis of SS, especially with anti-Sjögren’s syndrome antigen A (SSA) and anti-SSB antibody negativity. Histopathology based on biopsy has clinical significance for disease stratification and prognosis evaluation, such as risk assessment for the development of non-Hodgkin’s lymphoma. Furthermore, histopathological changes of salivary gland may be implicated in evaluating the efficacy of biological agents in SS. In this review, we summarize the histopathological features of salivary gland, the mechanism of histopathological changes and their clinical significance, as well as non-invasive imaging techniques of salivary glands as a potential alternative to salivary gland biopsy in SS.